2000
DOI: 10.1209/epl/i2000-00325-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for competing orderings in strontium titanate from hyper-Raman scattering spectroscopy

Abstract: The frequencies of the softest polar optic phonons of tetragonal SrTiO3 are accurately determined using high-resolution hyper-Raman spectroscopy on oriented-domain crystals. The splitting of the polar soft mode in the tetragonal phase is quantitatively related to the 105 K structural transition, i.e., to the rotation of the oxygen octahedra and to the associated macroscopic strains. In addition to quantum fluctuations, these tetragonal distortions are found to be essential in preventing the ferroelectric trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(107 citation statements)
references
References 33 publications
7
94
0
6
Order By: Relevance
“…3 is their temperature dependence. The frequencies do not change appreciably with T , and no phonon softening is observed which may indicate displacive ferroelectricitynot even incipient as in SrTiO 3 [30]. Moreover, we do not observe any appreciable shift in the ω j 's around or below the FM transition.…”
Section: Experiments and Resultsmentioning
confidence: 47%
“…3 is their temperature dependence. The frequencies do not change appreciably with T , and no phonon softening is observed which may indicate displacive ferroelectricitynot even incipient as in SrTiO 3 [30]. Moreover, we do not observe any appreciable shift in the ω j 's around or below the FM transition.…”
Section: Experiments and Resultsmentioning
confidence: 47%
“…14) In addition, a value of about 40,000 has been estimated using hyper-Raman scattering measurements. 14,15) Our (100) plate sample with a maximum value of 36,000 was estimated to be a monodomain crystal, which required the introduction of a secondary order parameter, associated with the structural Prior to the analyses using quantum mechanical formulae, the temperature dependence of ε ′ measured at 10 kHz above 150 K was analyzed using the classical Curie-Weiss formula, Table II.…”
Section: Analyses Based On Vendik's Formula and Comparison With Thosementioning
confidence: 99%
“…In order to enhance the polarization, a buffer layer such as SrTiO 3 has been taken into account. A lot of work devoting to calculation of lattice dynamics of perovskite thin film of SrTiO 3 indicated that ferroelectric instability arising in thin film of SrTiO 3 on the substrate [8,9]. Sadovskaya et el.…”
Section: Introductionmentioning
confidence: 99%